Modeling and control of two-link snake. (13th March 2018) - Lipták, Tomáš; Virgala, Ivan; Miková, L'ubica; Galajdová, Alena; Tuleja, Peter; Koukolová, Lucia; Varga, Jozef; Sukop, Marek
This article deals with using of geometric mechanics at modeling mixed mechanical locomotion systems. In introductory part, the division of locomotion systems and reduced motion equation, which create the mathematical model of the system, is analyzed. Further we devoted to example of mixed locomotion system—two-link snake. We created the mathematical model of this example, simulated this system, and represented other tools of geometric mechanics.